Women and the new business leadership - Thomson, Peninah; Lloyd, Tom. (Houndmills, Basingstoke, Hampshire, UK : Palgrave MacMillan, 2011)
'In'The Woman's Place is in the Boardroom' the authors put the business case for more women on company boards. In the next book they explained how to acheive it. Here the authors discuss the role women directors can play in the reform of corporate governance systems following recent financial, crises in leadership, governance and the economy'--
Includes bibliographical references (p. 167-172) and index.
Keywords: Women executives; Businesswomen